2020
DOI: 10.1037/spq0000390
|View full text |Cite
|
Sign up to set email alerts
|

The SSIS SEL Brief Scales–Student Form: Initial development and validation.

Abstract: The SSIS SEL Brief Scales-Student Form (SSIS SELb-S) was developed to create an efficient assessment of students' social and emotional learning (SEL). Using item response theory with ratings from 800 students in Grades 3-12 from the standardization sample, 20 items were selected from the full-length SSIS SEL Rating Form -Student to maximize score information and rating efficiency. After identifying items for the SSIS SELb-S, we conducted several reliability and validity analyses. These analyses provided initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 30 publications
0
34
0
Order By: Relevance
“…Potential uses for the SSIS SEL b ‐S as suggested by Anthony et al (2020a) include using the scores to inform intervention planning, progress monitoring, and as a universal screener for social and emotional skills. As with the SSIS SEL b ‐T, IRT was used to select 20 items from the SSIS SEL‐RF‐S and Anthony et al (2020a) tested the reliability and validity of the SSIS SEL b ‐S scores on data from the SSIS Rating Scale standardization. Anthony et al (2020a) found that the SSIS SEL b ‐S scores had sufficient evidence of reliability.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Potential uses for the SSIS SEL b ‐S as suggested by Anthony et al (2020a) include using the scores to inform intervention planning, progress monitoring, and as a universal screener for social and emotional skills. As with the SSIS SEL b ‐T, IRT was used to select 20 items from the SSIS SEL‐RF‐S and Anthony et al (2020a) tested the reliability and validity of the SSIS SEL b ‐S scores on data from the SSIS Rating Scale standardization. Anthony et al (2020a) found that the SSIS SEL b ‐S scores had sufficient evidence of reliability.…”
Section: Methodsmentioning
confidence: 99%
“…As with the SSIS SEL b ‐T, IRT was used to select 20 items from the SSIS SEL‐RF‐S and Anthony et al (2020a) tested the reliability and validity of the SSIS SEL b ‐S scores on data from the SSIS Rating Scale standardization. Anthony et al (2020a) found that the SSIS SEL b ‐S scores had sufficient evidence of reliability. Specifically, Cronbach's ɑ was .90 for the SEL Composite with scale values ranging from 0.64 to 0.71 (median = 0.69).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, the CASEL model has influenced SEL policies in all 50 US states and internationally (Dusenbury, Yoder, Dermody, & Weissberg, 2019;Eklund, Kilpatrick, Kilgus, & Haider, 2018). Recent studies have also corroborated the CASEL framework as a broad model of important SEL skills (Anthony, Elliott, DiPerna, & Lei, 2020a, 2020bDoromal, Cottone, & Kim, 2019), further supporting the utility of this framework. Despite these developments, there remain important barriers to effective practice in contemporary school-based service delivery paradigms, such as MTSS.…”
mentioning
confidence: 92%